2005
DOI: 10.1007/s00535-005-1592-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic assessment of gastric motility in diabetic gastroparesis before and after attaining glycemic control

Abstract: These findings suggest that attaining glycemic control improves gastric motility and attainments upper abdominal symptoms in diabetic patients with gastroparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
0
22
0
2
Order By: Relevance
“…[21][22][23][24] Also, delayed gastric emptying will lead to gastrointestinal symptoms, such as early satiety, postprandial fullness, epigastric pain, nausea, and vomiting. [21][22][23][24][25][26] Although these GI symptoms are not considered to be important causes of mortality in T2DM, they have obvious negative influences on diabetes control, diabetes complications, and health-related quality of life. 23,27,28 In our study, both TAS30QW (nausea, 83.20%; vomiting, 88.52%) and LIX30BID (diarrhea, 84.76%) had higher risk for GI AEs when compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Also, delayed gastric emptying will lead to gastrointestinal symptoms, such as early satiety, postprandial fullness, epigastric pain, nausea, and vomiting. [21][22][23][24][25][26] Although these GI symptoms are not considered to be important causes of mortality in T2DM, they have obvious negative influences on diabetes control, diabetes complications, and health-related quality of life. 23,27,28 In our study, both TAS30QW (nausea, 83.20%; vomiting, 88.52%) and LIX30BID (diarrhea, 84.76%) had higher risk for GI AEs when compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…A hipótese de que o controle inadequado da glicemia é a principal causa de sintomas gastrointestinais tem sido levantada em alguns estudos 17,43,44 . É comprovada pelas alterações associadas entre mudanças agudas nos níveis da glicemia e motilidade 12,31,43 .…”
Section: Como a Hiperglicemia Causa Sintomas Gastrointestinais No Dm?unclassified
“…É comprovada pelas alterações associadas entre mudanças agudas nos níveis da glicemia e motilidade 12,31,43 . Variações agudas na glicose sérica, mesmo nos limites das taxas normais, podem ter grande influência na função motora e sensitiva do trato digestório 17,42 .…”
Section: Como a Hiperglicemia Causa Sintomas Gastrointestinais No Dm?unclassified
“…In this regard, an ultrastructural study of the gastric wall showed alterations in the axoplasma of the nerve fibres (reduction of the neurotubules and of the neurofilaments, swelling of the mitochondria, lipofuscin deposits) and accumulation of elastic fibres and collagen around the nerve endings, which separate them from the smooth muscle cells [43]. In other diseases characterized by autonomic nervous alterations, such as diabetes mellitus, an impairment in gastric wall motility has been described by ultrasonography and other methods [44][45][46]. No significant differences in gastric motility between different subsets of SSc patients were observed: gastric filling and emptying were impaired at the same degree in patients with diffuse and limited cutaneous SSc, as well as in patients with anti-centromere and anti-Scl70 ANA specificity.…”
Section: Discussionmentioning
confidence: 95%